The moderating effects of board equity ownership on the relationship between enterprise risk management (ERM) practices and the performance of financial institutions in Nigeria - Idris, Ahmed (2017)
Corporate failure around the world has triggered scholars and professionals to re-examine the link between risk management practices and performance of organizations. The prime objective of this study is to examine the impact of enterprise risk management (ERM) framework implementation and ERM success factors include compliance (COP), risk management culture (RMC), risk management information (RMI), risk knowledge sharing (RKS), staff competence (SC), organisational innovativeness (OIN) and leadership factor (LF) on the performance of financial institutions in Nigeria. The study also aims to determine the moderating effect of board equity ownership (BEO) on the relationship between risk management framework (RMF) implementation, ERM success factors, and performance of financial institutions. Survey data on 163 randomly selected firms from five subsectors of financial institutions were collected. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test hypotheses. The findings of the study reveal that RMF, COP, RMC, RMI, RKS, SC, and LF have positive and significant effects on the performance of financial institutions. Contrary to expectation, OIN negatively influences the firm performance. Furthermore, BEO moderates positively the relationship between RMF, COP, RMI, RKS, and firm performance. However, BEO does not have significant moderating effects on RC, SC, OIN, and LF. The results of this study offer valuable insight to financial institutions, regulators, and researchers to further understand the effects of ERM practices on firm performance. The study recommends that firms and regulatory agencies should promote sound risk culture with a view to increase risk awareness, establish a robust information management system for comprehensive risk analysis and reporting, devise internal risk knowledge sharing strategies to boost staff capabilities and entrench effective leadership role to handle complex firms’ operational activities.